IMPLEMENTASI PERIZINAN ROKOK DI KOTA BATAM BERDASARKAN PASAL 31 PERATURAN PEMERINTAH REPUBLIK INDONESIA NOMOR 41 TAHUN 2021 TENTANG PENYELENGGARAAN KAWASAN PERDAGANGAN BEBAS DAN PELABUHAN BEBAS - Arsyah, Nabila Aulia; Indra, Mexsasai; Akmal, Zainul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Free Trade Zone or commonly called FTZ is one of the containers in the SpecialEconomic Zone (SEZ) which is related to a free trade zone that provides access for thecountry in terms of exemption from import duties, Value Added Tax (VAT), Value Added Taxand Luxury Goods (STLG), and excise. The access granted by a country creates a policy thatmust be implemented, such as licensing. This is confirmed in the Regulation of the Head ofthe Batam Free Trade Zone and Free Port Regulatory Agency Number 8 of 2019 concerningthe Implementation of the Entry and Exit of Goods To and From the Free Trade Zone andFree Port of Batam Article 27 Paragraph (3), where every activity in the FTZ area must havea license, one of which is licensing the distribution of cigarettes.The high contribution of cigarettes and the existence of large profits, makes a problemarise, namely the case of illegal cigarettes. So that the state issued Government Regulation ofthe Republic of Indonesia Number 41 of 2021 concerning the Implementation of Free TradeAreas and Free Ports as a juridical basis for its implementation. This is considered importantso that state revenue related to cigarette excise, especially in Batam City, can beimplemented properly and maximally.Based on the results of temporary observations, the implementation of PP No. 41 of2021 concerning the Implementation of Free Trade Areas and Free Ports has not gone asexpected. This is based on the presence of companies that do not have distribution licensesissued by BP Batam, so that it was found that 68% of the number of cigarettes did not havedistribution licenses with a projected state loss of IDR 78.8 billion, so that the target of staterevenue is not in accordance with the number of cigarette distribution activities.Keywords: Free Trade Zone, Excise, Illegal Cigarettes.